Haemolytic Disease of the Newborn (KYAMC Journal, 2023)
Background: Immune-mediated haemolytic disease of the newborn refers to a specific category of haemolytic anaemia that results from transplacental passage of IgG antibodies from a pre-sensitized mother to her fetus in utero. This occurs due to blood group incompatibility between the mother and the fetus. The clinical presentation covers a wide spectrum spanning from still births and erythroblastosis fetalis as well as infants born with only mild haemolysis to those having severe anaemia snd severe indirect hyperbilirubinaemia followed by hydrops.Objective: We describe the journey of a Rh-D negative mother who endured through six pregnancies in order to have a healthy baby.Conclusion: To highlight the importance of blood grouping and Rh typing during the first antenatal visit and subsequent monitoring of antibody titers, especially in a mother who is Rh-D negative.KYAMC Journal Vol. 14, No. 01, April 2023: 54-56